Fabrication of High‐Performance Devices on Water‐Soluble Lead Halide Perovskites Using Water‐Based Photolithography. Issue 6 (9th December 2022) - M. A., Gokul; Rahman, Atikur
Abstract: The alluring optoelectronic properties of lead halide perovskites have continued to attract enormous interest from the scientific community. They are among the brightest candidates for future optoelectronic devices. However, making active devices out of single nano/microcrystals of lead halide perovskites has been a major hurdle and this has dulled its position as a future optoelectric material considerably. The notoriety of not withstanding the steps in photolithography is at the core of this problem. Here, a noninvasive sacrificial layer‐assisted photolithography technique is reported to successfully make active nano/microdevices on single nano/microcrystals of water‐soluble lead halide perovskite. The sacrificial layer can easily be removed without altering the photoresist patterns which makes it possible to fabricate complex high‐performance devices on water‐soluble samples. It is believed that this technique can easily integrate with existing technologies and can elevate the research and application in the field of lead halide perovskites and other water‐soluble materials to new heights. Abstract : Highly water‐soluble nature of lead halide perovskite makes it impossible to do conventional photolithography on these materials. This has been a bottleneck for micro device/sensor fabrication of these crystals. The work overcome this challenge by adding a sacrificial layer that protects the crystal during photolithography which can be removed by washing in toluene without damaging the lithography pattern.